2016
DOI: 10.1097/md.0000000000003314
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-Like Follicular Carcinoma of the Kidney in a Patient with Skull and Meningeal Metastasis

Abstract: Thyroid-like follicular carcinoma of the kidney (TLFCK) is an extremely rare subtype of renal cell carcinoma with close resemblance to the well-differentiated thyroid follicular neoplasms. TLFCK has not been included in the 2004 World Health Organization (WHO) classification due to the limited data available. Only 27 cases have been reported in the literature to date.Herein, we report a unique case of TLFCK that presented as a striking skull and meningeal metastasis 5 years after the initial diagnosis; this is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…The tumour size is variable, ranging from 11 to 118 mm in the greatest dimension. Thyroid‐like follicular carcinoma of the kidney usually follows a non‐aggressive and indolent clinical course, although several patients with metastases in the regional lymph nodes, lung, retroperitoneum, skull and meninges have been reported …”
Section: Thyroid‐like Follicular Carcinoma Of the Kidneymentioning
confidence: 99%
See 1 more Smart Citation
“…The tumour size is variable, ranging from 11 to 118 mm in the greatest dimension. Thyroid‐like follicular carcinoma of the kidney usually follows a non‐aggressive and indolent clinical course, although several patients with metastases in the regional lymph nodes, lung, retroperitoneum, skull and meninges have been reported …”
Section: Thyroid‐like Follicular Carcinoma Of the Kidneymentioning
confidence: 99%
“…Thyroid-like follicular carcinoma of the kidney usually follows a non-aggressive and indolent clinical course, although several patients with metastases in the regional lymph nodes, lung, retroperitoneum, skull and meninges have been reported. [31][32][33][34][35][36] Grossly, thyroid-like follicular carcinoma of the kidney appears well-circumscribed and encapsulated, and the cut surface is tan-brown to dark brown. On microscopy, there is a distinct follicular pattern and thyroid-like morphology, with variable-size follicles filled with colloid-like content, resembling follicular carcinoma of the thyroid (Figure 2A-F).…”
Section: Thyroid-like Follicular Carcinoma Of the Kidneymentioning
confidence: 99%
“…Thyroid-like follicular renal cell carcinoma (TLFRCC) is a rare histopathological entity initially described in the literature in 2006 (Jung et al 2006). Since then, several cases have been published (Dong et al 2016), mostly describing well-circumscribed resected renal masses. In general, TLFRCC exhibits histology similar to thyroid follicular carcinoma, including PAX8 immunopositivity seen in both renal and thyroid tumor, although it is expected to be negative for thyroid immunohistochemical markers (e.g., TTF1, thyroglobulin).…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid follicular carcinoma usually metastasizes to the lungs and bone, rarely to the kidney. In addition, the tumor shows a positive reaction of thyroidspecific markers TTF-1 and TG [8]. The available data indicated that TLFRCC immunohistochemical staining shows a consistent expression of the transcription factor PAX8, and a typical negative performance of thyroid immunohistochemical markers, which is significant to the identification of thyroid metastatic tumors.…”
Section: Discussionmentioning
confidence: 86%
“…TLFCK is a kind rare pathological type of renal tumor, which is potentially considered origining in the renal parenchymal urinary tubule epithelial system [1]. This unique histopathological type of RCC(renal cell carcinoma), described firstly in 1996 by Angell et al, had not been recorded in the 2004 world health organization in account of the lack of sufficient clinical evidence that only 28 cases reported in the English literature to date [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. TLFCK has a similar feature with the follicular carcinoma of the thyroid in morphology.…”
Section: Introductionmentioning
confidence: 99%